An overview of insect innate immunity. Issue 6 (29th June 2020) - Ali Mohammadie Kojour, Maryam; Han, Yeon Soo; Jo, Yong Hun
Abstract: Due to the exposure of insects to various sources of pathogens during different stages of their life cycle and their vulnerability towards subsequent infections, moreover lack of morality issues, economical breeding and short‐term‐life cycle, insect's immunity has been considered as a high‐potential candidate to study underlying mechanisms of defense responses against all sort of invaders, as well as pandemic diseases. Currently, the world is enduring monumental pressure to meet global food production demands. One viable option would be to mass rear edible insects, such as coleopteran meal worm Tenebrio molitor, which is thought to be a substantial protein source. In addition, using antimicrobial peptides as an alternative for antibiotic source against multidrug‐resistant pathogens, makes insects a valuable option to solve this health issue. As a consequence, sufficient knowledge of insect immunity will lead us to reach advanced diagnostic and treatment technologies. To accomplish these goals, crucial importance of identification and functional characterization of the main signaling pathways, such as Toll and immune deficiency (IMD), prompted us to review the mechanisms of the signaling pathways involved in immune response in well‐known insect models.